Association of marine Collagen/Biosilicate composites and photobiomodulation in the process of bone healing using an experimental model of calvarial defect (Research, Society and Development, 2021)
The study comparing the bone regenerative capacity in an experimental model of cranial bone defects in rats, into 3 groups: G1: bone defects irradiated with photobiomodulation; G2: Biosilicate + photobiomodulation and G3: Biosilicate and Spongin + photobiomodulation. Histocompatibility and bone responses were performed after 15 and 45 days of implantation. Histological analysis demonstrated that photobiomodulation irradiated animals presented an increased amount of newly formed over time. Histomorphometry showed higher values for bone volume for G3 and G1, higher values for osteoid volume and number of osteoblasts observed for G3 compared to G2. TGF-β immunolabelling was higher for G2. The values found for VEGF were higher for biosilicate (with or without spongin) 15 days of implantation with an increased difference being observed for G1, 45 days after surgery. In conclusion, the stimulus provided by photobiomodulation associated to the biomimetic composite increased bone formation in the cranial bone defect in rats. Consequently, these data highlight the potential of the introduction of spongin into biosilicate and irradiated with photobiomodulation to improve the biological performance for bone regeneration applications.